Cell line-dependent release of quasi-enveloped hepatitis E virus reveals alternative Golgi-associated egress in the absence of pORF3 - Gremmel, Nele; Glitscher, Mirco; Scholz, Johannes; Gadicherla, Ashish; Johne, Reimar; Hildt, Eberhard; Becher, Paul (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHepatitis E virus (HEV) particles are released from infected cells in a quasi-enveloped form, typically via the multivesicular body (MVB) pathway, which is mediated by the viral accessory protein pORF3. However, cell-type specific aspects of this release mechanism remain poorly understood.MethodsWe analyzed the release and envelopment characteristics of a pORF3-deficient genotype 3c HEV (HEVΔORF3) in comparison to wild-type HEV (HEVwt) in two human cell lines: hepatoma-derived PLC/PRF/5 and lung carcinoma-derived A549/D3 cells.ResultsWhile viral release of HEVΔORF3 was strongly impaired in A549/D3 cells, PLC/PRF/5 cells supported efficient viral release despite the absence of pORF3. In PLC/PRF/5 cells, HEV particles retained quasi-envelopment and utilized an alternative, Golgi-associated egress pathway in the absence of pORF3. In contrast, A549/D3 cells did not support this compensatory release route.ConclusionOur findings highlight a pronounced cell line-dependent variability in HEV release pathways, emphasizing the importance of cellular context in studies of HEV biology and antiviral strategies targeting virus egress.